Prevalence of Waterborne Diseases in Sudoorpashchim Province - Pant, Narendra Raj; Bhatt, Kabita; Joshi, Hem Raj (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Unsafe drinking water, poor sanitation, and lack of personal hygiene are the major causes of waterborne diseases. Water-induced health problem includes typhoid, acute gastroenteritis, diarrhea, dysentery, and hepatitis. In the Sudoorpashchim province, people suffer from these water-related diseases, and the frequency of the problem is intense in the summer. The objective of this study was to determine the frequency of waterborne diseases in Sudoorpashchim province, far western region of Nepal. Methods: The data was collected from the provincial health directorate at Dipayal and analysed using the Origin 2010 software Results: The findings reveal that the prevalence of waterborne diseases gradually decreased as compared to last four to five years and attended 5.6% in FY 2019/2020, signifying an improvement in the personal hygiene of the people. Conclusions: The prevalence of waterborne diseases sharply decreased in the FY 2019/2020, indicate the rectification in the personal hygiene of people.